Knowledge, attitudes and practices of medical researchers toward authorship in scientific journals - More, Balaji D.; More, Anju B.; Suthar, Harsh J. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The knowledge, attitudes and practices of scientific authorship vary across different regions. We conducted this study to understand this variation among medical researchers in India. Methods: An anonymous web-based researcher-survey invited all faculty, researchers and PhD students at Pacific institute of Medical sciences, Udaipur, India. The study design and the questionnaire were approved by the institutional ethics committee. Basic information on study was given to obtain consent for participation. The 30 questions on authorship experience and related issues were based on the statements in International Committee of Medical Journal Editors (ICMJE) and other national and international recommendations on authorship. Participants reported their authorship experiences and answered multiple choice questionnaires. Results: The response rate was 36.36% among the participants, who were post-graduate with up to 10 years of research experience. About 62.5% had not been appropriately acknowledged as authors at some point during their career. Contributors (authorship) and ethical peer review is perceived as the key principle of research integrity. Though, single authorship was regarded as more significant, interdisciplinary management of diseases increases number of co-authors. A platform to challenge authorship, declaration of contribution in authorship and shared responsibility of co-authors in case of fraudulent publication was majority opinion. Conclusions: Almost 50 of the participant medical researchers had knowledge of formal authorship requirements. Majority agreed with the criteria would help in decreasing the authorship dispute in the medical research. There is need for awareness and continuous education on these criteria.